The influence of temporal parameters on foreign accent - Horga, Damir; Mildner, Vesna (2004)
Speakers of foreign languages usually speak with an accent that may be revealed at various levels - from the phonetic-articulatory to the pragmatic-nonverbal level. The aim of the present study was to investigate the temporal characteristics of English spoken by Croatian speakers as L2 and to show which of the temporal characteristics are the best predictors of their pronunciation proficiency. The results are presented in two parts (a) as tempral differeces between English spoken by Croatian speakers and native English speakers ; and (b) as temporal characteristics which contribute to the foreign accent of Croatian speakers when they speak English. Not all variables in which the native and Croatian speakers of English differ significantly are equally good predictors of foreign accent. Of the segmental variables, consonants are better predictors than the vowels, and among consonants stops and fricatives are the most prominent. Suprasegmental variables in general, and tempo and hesitations in particular, are good predictors of foreign accent.
Projekt MZOS
Projekt MZOS
ENG